Why does female voters prefer vote buying in local head elections? - Yanti, Mery; Malinda, Febrimarani; Tamsyah, Indra (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This study aims to analyze the determinants of vote buying preferences among female voters in local head elections. We identify eight independent variables (education, income, welfare, happiness, risk-taking attitude, place of residence, age, and marital status) as a predictor of Y. This research used the 5th Indonesian Family Life Survey (IFLS) data, which was collected by Rand Corporation, Ltd., during 2014 – 2015 in 13 (thirteen) provinces in Indonesia. The data were analyzed by logistic regression technique using STATA 15. The results showed that only four independent variables had a statistically significant relationship with Y: education level, risk-taking attitude, income level, and marital status. These four independent variables can explain Y by 2.48% significantly, X2 (4) = 357.23, p < 0.01. At the variable level, all variables have a negative relationship with Y, except for marital status (142%) which has the largest contribution to explain Y. The effect of income, risk-taking attituted, and education on Y respectively is 90.62%, 80.90%, 31.11%. The final model of logistic regression produces the characteristics of female voters who tend to choose candidates local head election due to money politics: education below senior high school/equivalent, married, poor, and not willing to take risks. The author recommends all governments at all levels continue the modernization process in all aspects of the social life of Indonesian citizens.